Descendants : Escape From the Isle of the Lost - Book 4 - De la Cruz, Melissa 1971- (Los Angeles Disney/Hyperion, 2019)
Mal and Uma have a score to settle, and they'll come face to face in an explosive underwater battle that could determine the fates of Auradon and the Isle of the Lost once and for all.
Keywords: Islands -- Juvenile fiction; Magic -- Juvenile fiction; Disney characters -- Juvenile fiction; Children of criminals -- Juvenile fiction; Villains -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Islands -- Fiction; Magic -- Fiction; Disney characters -- Fiction; Children of criminals -- Fiction; Villains -- Fiction; Quests (Expeditions) -- Fiction; Fantasy; Fantasy